DEVELOPMENT OF INNOVATION IN TEACHING MANAGEMENT IN THE ERA OF ARTIFICIAL INTELLIGENCE FOR PHRA PARIYATTI DHAMMA GENERAL EDUCATION SCHOOL, BANGKOK - Saensuk, Sawanathakorn; PhrakhruOpatnontakitti; Ngamprakhon, Sin (Journal of Educational Review Faculty of Education in MCU, 2026)
The objectives of this research were to: 1) to examine the current state of teaching and learning in Buddhist Pariyatti schools (General Education Division) in Bangkok..2) to develop an instructional innovation using Artificial Intelligence (AI) for Buddhist Pariyatti schools (General Education Division) in Bangkok . 3) to implement the AI-based instructional innovation; and. 4) to evaluate the use of the AI-based instructional innovation in Buddhist Pariyatti schools (General Education Division) in Bangkok. The study employed a research and development (R&D) methodology, conducted in four phases. Phase 1 involved studying the current conditions of teaching and learning among 193 participants, and analyzing the data using percentage, mean, and standard deviation. Phase 2 focused on developing the model through interviews with 12 key informants, content analysis, drafting the model, and conducting a focus group discussion with nine experts. Phase 3 examined the use of the model through a workshop with 20 school administrators, with data analyzed using mean and standard deviation. Phase 4 evaluated the model by collecting feedback from 193 experts comprising administrators and teachers in Buddhist Pariyatti schools (General Education Division), and analyzing the data using mean and standard deviation. The research results showed that 1) The current state of teaching and learning in Buddhist Pariyatti schools (General Education Division) in Bangkok was at a high level overall. All aspects were rated highly, ranked from highest to lowest as follows: learning content, learning activities, learning media and innovation, and assessment and evaluation. 2)The developed innovation consisted of five components - rationale, objectives, systems and mechanisms, operational procedures, and success conditions - based on the Design Thinking process, which includes Empathize, Define, Ideate, Prototype, and Test. Four sets of workshop activities were also developed to support the use of AI in lesson design, learning activities, media development, and assessment. 3) The examination of the model’s implementation showed that participants in the workshop rated the model at the highest level. 4) The evaluation of the AI-based instructional innovation model indicated that the overall assessment was at the highest level. The research synthesized a conceptual framework known as the “AICAMIME MODEL” consisting of: AI = (Artificial Intelligence), C = (Contextual), A = (Activities), MI = (Media and Innovation), ME = (Measurement and Evaluation)